Genome-wide characterization of respiratory burst oxidase homolog (RBOH) in soybean [(glycine max l. Merr.)] - Quang, Ong Dang; Thao, Nguyen Phuong (Vietnam Journal of Biotechnology, 2018)
Plant respiratory burst oxidase homologs (RBOHs), also known as NADPH oxidase (NOX) have involved as a key producers of reactive oxygen species (ROS) in a wide range of biological processes, including plant growth, development, and abiotic stress responses. In this work, a total 17 soybean RBOH encoding genes (GmRBOHs) were identified. Furthermore, their domain architecture, chromosomal distribution, gene structure, gene duplication, and phylogenetic analysis were carried out. Phylogenetic tree divided the RBOHs from soybean, another legume plants (Phaseolus vulgaris), and Arabidopsis into six subfamilies, with soybean RBOH genes distributed in subfamily I to VI. All RBOH proteins of soybean contained four major domains, which focused on EF-hands domains with Ca2+-binding residues provided more insights into function of RBOH proteins in soybean. The differential expression pattern using RNA-seq of 17 RBOH genes in soybean indicated that most of the genes express in root and nodule; among them, GmRboh9 and GmRboh12 have the highest expression. The analysis presented provides a scientific basis for further research on function of RBOH genes in soybean.